EFFECT OF CHEMICALS AND GROWTH REGULATORS ON GERMINATION, VIGOUR AND GROWTH OF PASSION FRUIT (PASSIFLORA EDULIS SIMS.) - N. GURUNG,; G. S. K. SWAMY,; S. K. SARKAR,; N. B. UBALE, (The Bioscan, 2013)
An experiment was conducted during 2010-2011 to study the effect of chemicals and growth regulators on germination, vigour and growth of passion fruit. The study showed significant differences among the treatments. Maximum germination percentage (84%) and germination index (2.02) was observed in seeds treated with thiourea 1 per cent. Maximum seedling height 16.23cm, 19.62cm and 20.91cm and number of leaves 10.25, 11.35 and 14.25 were observed in seeds treated with GA3 500 ppm at 30, 60 and 90 days respectively. Vigour index-I (1547.34 cm) and Vigour index-II (128.76 g) were recorded maximum in GA3 500 ppm treated seeds. Also, the maximum fresh and dry weights of shoot were 3.76 g and 0.98 g respectively in GA3 500 ppm treated seeds. The use of growth regulator is therefore recommended as an approach for propagation of passion fruits.